Analisis Tingginya Turnover Karyawan sebagai Faktor Penghambat Peningkatan Kinerja SDM pada Sektor Industri Kuliner : Studi Kasus pada UMKM Lupi Bakery, Desa Lopang, Kecamatan Kembangbahu, Kabupaten Lamongan - Sofi Alya Farisa (GEMILANG: Jurnal Manajemen dan Akuntansi, 2026)
This study aims to analyze the factors that cause high employee turnover rates and their impact on improving human resource (HR) performance in the culinary industry. The research methods used include field observation, documentation analysis, and in-depth interviews with owners and employees of several culinary businesses. The results indicate that high turnover is caused by the absence of standard operating procedures (SOPs), a lack of training and competency development programs, and low work motivation due to a lack of recognition and welfare. High employee turnover has various negative impacts, including reduced team stability, increased recruitment and training costs, decreased customer service quality, and weakened productivity and operational effectiveness. Furthermore, the repeated adaptation process that new employees must undergo hinders the achievement of long-term performance targets. Therefore, a more comprehensive HR management strategy is needed, including the implementation of clear SOPs, improved employee welfare and motivation, and the implementation of ongoing training and retention programs to support the growth and competitiveness of culinary businesses amidst the dynamics of a competitive industry.